Synthesis of a novel bismuth molybdite/iron oxide thin film for oxytetracycline degradation in a photoelectrocatalytic system - Pastrana, Elizabeth C.; Valdivia-Alvarez, Daniel; Radenovich, Italo Espinoza; Gonzales-Lorenzo, Carlos D.; Wang, Dunwei; de Brito, Juliana Ferreira [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Alarcón, Hugo A. (Elsevier, 2024)
In this study, heterostructures based on Bismuth molybdite/iron oxide (Bi2MoO6/Fe2O3) thin films were fabricated by a dip-coating technique using precursor solutions. The heterostructures were deposited on fluorine-doped tin oxide glass substrates. From a detailed characterization using X-ray diffraction and X-ray photoelectron spectroscopy, the formation of the orthorhombic phase for Bi2MoO6 and the co-existence of hematite and maghemite in Fe2O3 was demonstrated. Meanwhile, the field emission scanning electron microscopy cross-section images confirm the formation of well-defined Bi2MoO6 film under the Fe2O3 deposition. The optical band gap energies for the heterostructure obtained were estimated from the diffuse reflectance spectra and ranged from 2.3 to 3.5 eV. Photoluminescence analysis revealed an improved separation and faster transfer of photogenerated electrons and holes for the Bi2MoO6/Fe2O3 (Het) film. The best oxytetracycline (OTC) removal percentage through photoelectrocatalytic treatment was 96.85% using the Het. Besides, were carried out the variation of parameters which affect the OTC photoelectrocatalytic degradation as pH, potential applied, and scavenger assay. The 1O2 was the oxidant predominate, which attack the OTC ring to initiate and accelerate the degradation process. Based on the analysis of degradation intermediates and characteristics of Bi2MoO6/Fe2O3, possible degradation pathways and mechanisms of OTC were displayed. An enhancement of oxytetracycline degradation efficiency of Het fabricated compared to pristine oxides was achieved mainly due to avoid the charge recombination of photogenerated electron-hole pairs provided by Direct Z-scheme heterostructure. Finally, the Het fabricated represents a promising material for efficient and sustainable pharmaceutical removal applications.
Keywords: Bismuth molybdite; Direct Z-scheme heterostructure; Iron oxide; Oxytetracycline